Performance of Type III stilling basins for stepped spillways - Frizell, K. W., author; Svoboda, C., author; Matos, J., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
Energy dissipation within hydraulic structures continues to be one of the major issues facing the designer of new or rehabilitated facilities, such as for overtopping protection of embankment dams. The energy dissipation characteristics of stepped spillways have been well documented, both for low- and high-head dams. Interestingly, much of the generalized research on stepped channels and spillways over the past few decades, while concerned with the amount of energy dissipated on the steps themselves, has contributed very little to generalized design criteria for terminal dissipation structures/stilling basins. Many site specific studies have included work on modifications to stilling basins to account for the increased energy dissipation on the steps, typically resulting in a shortening of the basin length. Others have included some stilling basin parameters within their studies. A few studies have attempted to provide generalized design guidance for the use of specific types of stilling basins with stepped chutes and spillways. This paper will focus on recent studies at the Reclamation laboratory that evaluated the application of smooth channel design criteria for Type III stilling basins to a variety of stepped spillway slopes. While there is a lack of specific generalized studies for stilling basin performance over the range of all types of stepped spillways that exist, there appears to be adequate data available to allow the designer to select and size an appropriate stilling basin for most types of stepped spillways currently in use, including RCC overtopping protection systems.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: energy dissipation; stepped spillways; stilling basin; Froude number